2015
DOI: 10.11604/pamj.2015.20.406.6206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, sociodemographic features and risk factors of Hepatitis B virus infection among pregnant women in Southwestern Nigeria

Abstract: IntroductionHepatitis B virus is responsible for 50%-80% of Hepatocellular carcinoma cases worldwide. In Nigeria, vertical transmission remains a major route of Hepatitis B virus infection. Primary (vaccines and post-exposure prophylaxis) and secondary prevention of HBV transmission by appropriate sexual and sanitary practices are not yet optimal in the country yet measures for early detection (serological, molecular) and treatment of infected pregnant women is not a practice. This study aimed at identifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
6
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 19 publications
9
36
6
6
Order By: Relevance
“…Our observation was in agreement to a previous conducted in Nigeria [25]. Moreover, pregnant women who had no employment and those who were married or cohabiting had high prevalence of HBsAg.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation was in agreement to a previous conducted in Nigeria [25]. Moreover, pregnant women who had no employment and those who were married or cohabiting had high prevalence of HBsAg.…”
Section: Discussionsupporting
confidence: 92%
“…The age group of 20 -29 years had the highest HBV sero-prevalence rate of 19.7% and followed by 30 -39 years 7.6%. This is in agreement with the highest viral hepatitis seroprevalence rate observed in the 25 -29 years' age group in a similar study in Ibadan, Nigeria [39]. This may be so because this age range falls within the sexually active age group and hence are more at high risk of having a sexual contact with an infected person [40].…”
Section: Discussionsupporting
confidence: 90%
“…This prevalence was lower than the studies reported from Osogbo, Nigeria, Gambia, Yirgalem Hospital, Ethiopia, Deder Hospital, Eastern Ethiopia, Hawassa University referral hospital, Southwestern Nigeria, Yaounde-Cameroon, Eastern Region of Ghana, Buea Health District, Cameroon, Juba Teaching Hospital, Republic of South Sudan, Myanmar-Thailand Border and Shaanxi, China in which the prevalence of HBV infection among pregnant women were 16.5%, 9.20%, 7.2%, 6.9%, 7.8%, 8.3%, 7.7%, 10%, 9.7, 11%,6.2% and 7.07% respectively [12,13,15,17,[23][24][25][26][27][28][29][30].…”
Section: Prevalence Of Hepatitis B Virus In Pregnant Womenmentioning
confidence: 99%